Roles of MIR155HG and TNF-α in Evaluation of Prognosis of Patients with Systemic Lupus Erythematosus: Associations of MIR155HG and TNF-α with Systemic Lupus Erythematosus - Gu, Xiaojing; Chen, Hu; Li, Rongping; Guo, Dibin (Journal of Medical Biochemistry, 2023)
Background: To study the roles of micro ribonucleic acid (miR)-155 host gene (MIR155HG) and tumor necrosis factor-α (TNF-α) in the evaluation of prognosis of patients with systemic lupus erythematosus (SLE).Methods: A total of 130 patients with SLE admitted to our hospital were selected, and the SLE disease activity index (SLEDAI) score was given. The expressions of MIR155HG and TNF-α were detected via quantitative reverse transcription-polymerase chain reaction (qRT-PCR), the incidence of complications during treatment was observed, and the associations of MIR155HG and TNF-α with SLEDAI before treatment and complications were analyzed. All patients were followed up after discharge, and the related factors to the prognosis of patients were analyzed via Cox regression analysis.Results: The levels of MIR155HG and TNF-α were higher in patients with an SLEDAI score of 10-14 points than those in patients with an SLEDAI score of 5-9 points and 0-4 points. MIR155HG and TNF-α were positively correlated with the incidence of infection, renal damage and cardiac damage. Moreover, there was also a positive correlation between the expressions of serum MIR155HG and TNF-α in SLE patients. SLEDAI score ≥10 points, complications during hospitalization, and highly-expressed MIR155HG and TNF-α were risk factors related to the prognosis of patients.Conclusion: MIR155HG and TNF-α are key regulators in the pathogenesis of SLE, and they can affect the prognosis of patients. Such a finding provides potential new targets for the treatment of SLE.
Keywords: Systemic lupus erythematosus; MIR155HG; TNF-α